Phytotherapeutics and Their Effects of Oral Health - K. Chytilová; J. Pazdera; P. Tvrdý (Czech Dental Chamber, 2010)
In the review the authors outline present knowledge on botanical characteristics of some plants and berrylike fruits (cranberry, blackberry, strawberry, grapevine, honeysuckle) and favorable effects of compounds they contain (protoanthocyanins, anthocyanins, ellagic acid, flavonoids) on oral health. Some of these favorable effects have been used in folk medicine in the past. At the present time these properties are the subject of intensive research and they have been also confirmed in tests performed in vitro. The attention is devoted especially to their anti-inflammatory, antibacterial and anticancer effects and their possible use in stomatology.